Odpowiedzi

2009-10-06T16:01:01+02:00
A) 3x-3=-x
3x+x=3 /:4
x= 3/4

b) 1-0,2x=0,3x
-0,2x - 0.3x= - 1
-0,5x= -1 /: -0,5
x=2

c) -7(x+2)+4=-3x
-7x - 14+4=-3x
-7x+3x= 14-4
-4x= 10 /:-4
x= -2,5

d) -4(½x-2)-4=2(-x+2)
-2x +8= -2x+4
-2x+2x=4-8
0x= - 4

e) 2x(x-1)=2(x-1)(x+3)
2x ( do kwadratu) -2x= 2* x (kwadrat) - 3
2x2 - 2x=2x2-3
2x2-2x-2x2=-3
-2x= -3
x=1,5

f) 1/3x+2=x
1/3x + x=-2
4/3x = -2 / : 4/3
x= -2/3

G) -7(2x+1)=4
-14x - 7=4
-14x=4+7
-14x= 11 / : -14
x= - 11/14
2009-10-06T16:10:18+02:00
A) 3(x-1) = -x
3x-3 = -x
3x+x=3
4x=3 |:4
x=¾
b) 1-0,2x=1
-0,2x-0,3x=1
-0,5x=1 |:(-0,5)
x=-2
c) -7(x+2)+4=-3x
-7x-14+4=-3x
7x+3x=10
10x=10 |:10
x=1
d)-4(½x-2)-4=-2x+4
-2x+8-4=-2x+4
-2x+4=-2x+4
-2x+2x=4-4
0=0
równanie tożsamościowe
e)2x(x-1)=2(x-1)(x+3)
2x²-2x=2(x²+3x-x-3)
2x²-2x=2x²+6x-2x-6
2x²-2x=2x²+4x-6
-2x-4x=-6
-6x=-6 |:(-6)
x=1
f)⅓x+2=x
⅓x-x=-2
-⅔x=-2 |*(-3)
2x=6 |:2
x=3
g)-7(2x+1)=4
-14x-7=4
-14x=4+7
-14x=11 |:(-14)
x=-¹¹/₁₄